Multi-stimuli responsiveness of pyrimidine bishydrazone: AIE, tuneable luminescence, white light emission, mechanochromism, acidochromism and its anticounterfeiting applications. (April 2023) - Anitha, Ottoor; Mathivanan, Moorthy; Tharmalingam, Balamurugan; Thiruppathiraja, Thangaraj; Ghorai, Sandipan; Natarajan, Ramalingam; Thiagarajan, Viruthachalam; Lakshmipathi, Senthilkumar; Murugesapandian, Balasubramanian
Abstract: The development of multifunctional properties associated with a single molecule being a centre of attention in the material science research area has been more focused in recent days. An aggregation-induced emissive (AIE) molecule having various aspects of stimuli-responsiveness such as mechanochromism, and acidochromism, along with white-light emitting behavior within a molecule will give rise to enormous applications in near future. A simple strategy to fabricate white-light emitting material from a single component system is beneficial for applications in the field of flat-panel displays and other optoelectronic devices. Herein, we have designed a D-A-D triad-based AIE active organic molecule HYPY-DESAL via a facile one-step Schiff-base condensation reaction between 4, 6-dihydrazinopyrimidine (HYPY ) and 4-( N, N -diethylamino)salicylaldehyde (DESAL ) containing ESIPT as well as ICT properties. This AIE-active molecule exhibits white light emission (fw  ≈ 49%) feature in addition to the tunable emission characteristics in its aggregated states which can be utilized for various light emitting diode applications. The compound revealed exceptional solid-state stimuli responsiveness such as mechanofluorochromism and acidochromism. HYPY-DESAL exhibited acidochromic features with a remarkable red shift in emission wavelength greater than 150 nm in the solid state. The specific site of protonation upon TFA addition was confirmed via 1 H NMR titration as well as TD-DFT experiments. The interesting reversible switching characteristics of the compound upon exposure to TFA/TEA are successfully utilized for several coding-decoding, information storage, and anti-counterfeiting applications in paper strips as well as PMMA-based thin films. Taken together, the combined features of the newly designed and readily accessible molecule exhibiting multi-stimuli responsive features such as AIE, tuneable luminescence, white light emission, mechanochromism, acidochromism, vapor phase sensing applicability using paper strips as well as thin films is unique, if not unprecedented. Graphical abstract: Image 1 Highlights: Multifunctional behavior of simple organic material, HYPY-DESAL has been discussed. HYPY- DESAL exhibits fabulous AIE features in DMSO/water mixtures incorporating tuneable luminescence and white light emission. Remarkable solid-state stimuli-responsive behavior such as mechanochromism and acidochromism was discussed. Extra ordinary red shift (Δλem, max >150 nm) was observed in HYPY- DESAL upon exposure to TFA. Reversible acidochromism exhibited by HYPY-DESAL was successfully employed for anti-counterfeiting applications.